“Hawan” bridging between ancient rituals and modern mental health therapy (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Notable abnormalities in behaviour, emotional control, or cognitive function are indicative of mental disorders, which are usually associated with suffering or impairment in important domains of functioning. Allopathic medicine, effectual, and mostly founded on ideas created by the ancient Greeks, forms the basis of many contemporary health systems worldwide, impeccable for ailments that require rigorous and rapid therapy. Nouvelle medications can effectively address a wide range of undesirable symptoms, permitting patients to resume their regular activities with little discomfort, ignoring its underlying causes. Equitable use of medicinal plants, especially in the form of herbal medicines, could significantly contribute to ensuring healthy lives and fostering wellbeing in light of the shortcomings of allopathic medicine. Conventional medicine may offer a different approach to treating different neurodegenerative conditions. Effective methods for management of Alzheimer's disease (AD) and other neurodegenerative disorders include a balanced lifestyle, excellent dietary habits, getting socio-psychological support, employing Rasayanas, Nasal Drug Delivery (aromatherapy), and performing "Hawan”, as defined by Ayurveda. Compared to conventional strategies, Nasal delivery has countless boons encompassing being non-invasive, having a quick commencement of action and having fewer detrimental effects owing to more engrossed  istribution. Since, it is delivered intra-nasally; it circumvents both the blood-brain barrier and the systemic first-pass effect, making it a potentially effective medication delivery method for the treatment of neurological illnesses like Alzheimer's disease, Epilepsy, Anxiety etc. The key for clinical professionals and psychiatrists is cautious integration, which includes respecting cultural traditions, monitoring herb-drug combinations, alerting patients to possible risks, and considering evidence-based complementary use in addition to conventional therapies.